2014
DOI: 10.2308/iace-50735
|View full text |Cite
|
Sign up to set email alerts
|

Satyam Fraud: A Case Study of India's Enron

Abstract: This case provides students a unique opportunity to examine and reflect on the challenges of auditing in today's global environment. Students examine a real-world billion dollar plus embezzlement and fraud at Satyam Corporation, an international company based in India and previously trading on the New York Stock Exchange. The case focuses on auditors' responsibilities related to obtaining and evaluating audit evidence, particularly as it relates to confirming cash and receivables. It also explores the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“… During the SEC's investigation of Satyam it was revealed that an interfirm review requested by PwC India raised concerns about the cash confirmation process, but that ultimately the Indian affiliates chose to ignore this feedback (SEC 2011; Brown et al 2014). The ability to ignore feedback raises questions regarding the enforceability of internetwork recommendations as well as members' ability to certify their own compliance with global network requirements.…”
mentioning
confidence: 99%
“… During the SEC's investigation of Satyam it was revealed that an interfirm review requested by PwC India raised concerns about the cash confirmation process, but that ultimately the Indian affiliates chose to ignore this feedback (SEC 2011; Brown et al 2014). The ability to ignore feedback raises questions regarding the enforceability of internetwork recommendations as well as members' ability to certify their own compliance with global network requirements.…”
mentioning
confidence: 99%
“…The company demonstrated an annual compound growth rate of 38% over that period. Similarly, operating profits, net profit and operating cash flows growth averaged 28,33 and 35%, respectively." Thus, Satyam generated significant corporate growth and shareholder value too.…”
Section: Case Study Of Creative Accounting Scam At Satyammentioning
confidence: 99%
“…The audits for a company of that size would have been staggered, with millions of dollars of outstanding receivables pouring in to different locations at any given time. As Veena et al [33] commented, "The Satyam case focuses on auditors' responsibilities related to obtaining and evaluating audit evidence, particularly as it relates to confirming cash and receivables. It also explores the quality control responsibilities related to audit procedures performed by foreign affiliates of a large international audit firm."…”
Section: Fake Audit and Dubious Role Played By Auditor'smentioning
confidence: 99%
“…The BMS case study was provided in the beginning of a 15-week semester. It was the last of six case studies that students had to analyze during the semester: Enron (Dharan and Bufkins, 2008); WorldCom (Kaplan and Kiron, 2007); Dell (Sandretto, 2011); Satyam (Brown, Daugherty, and Persellin, 2014); and Groupon (Dutta, Caplan, and Marcinko, 2014). Students learned how these companies had misapplied GAAP in recognizing revenues in their financial statements.…”
Section: Case Administrationmentioning
confidence: 99%